2017
DOI: 10.1016/j.bjid.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and vitamin D concentration: the challenges in taking care of children and adolescents infected with HIV

Abstract: Patients infected with HIV are at risk for BMD alterations and lower vitamin D serum concentrations; both of these variables should be evaluated at routine examinations in order to improve both prevention and therapeutic planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…They also agree that adequate ingestion and serum micronutrient monitoring can prevent disorders in bone metabolism and benefit children or adolescents who already have some type of impairment in this tissue 8,13,14 . Although Lima et al 7 found no significant relationship between low BMD and calcium intake.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…They also agree that adequate ingestion and serum micronutrient monitoring can prevent disorders in bone metabolism and benefit children or adolescents who already have some type of impairment in this tissue 8,13,14 . Although Lima et al 7 found no significant relationship between low BMD and calcium intake.…”
Section: Resultsmentioning
confidence: 88%
“…All the articles selected for the theme (1) 7,8,13,14 (Chart 1) agreed that children who lives with HIV present or may present alterations in bone metabolism, whether due to infection or associated with HAART.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported low bone mineral density (BMD) with increased risk of osteoporosis, osteopenia and, osteomalacia in HIV-infected individuals, including men, women, younger and older patients and vertically infected children [ 7 - 16 ]. A recent study evaluating 58 HIV-infected children and adolescents between the ages of 5.3 to 18.3 years, including 63.3% girls found an increased risk for lower BMD and lower levels of vitamin D serum concentration [ 17 ] and the loss in BMD is associated with the levels of vitamin D binding protein [ 18 ]. These and other studies [ 19 ] suggest that vitamin D levels should be included in the overall evaluation of HIV-infected patients.…”
Section: Hiv Infection and Bone Mineral Densitymentioning
confidence: 99%
“…CBD risk is increased in perinatally-acquired HIV independent of traditional CBD risk factors [4649**], possibly leading to premature osteoporosis and fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Low phosphate in turn stimulates parathyroid hormone release [53]. Although this should increase vitamin D hydroxylation and activation, TDF interferes with vitamin D activation in the kidney, further stimulating secondary hyperparathyroidism [46, 48, 54]. Excessive parathyroid hormone activity inappropriately increases osteoclast and decreases osteoblast differentiation resulting in increased bone resorption and reduced formation of new bone matrix.…”
Section: Introductionmentioning
confidence: 99%